HAK PERNIKAHAN PENGUNGSI ROHINGYA DI INDONESIA - Sari, Fitri Amalia (Indonesian Law Journal, 2024)
The UN Refugee Agency (UNHCR) reports that the number of Rohingya refugees who have come to Indonesia since November 2023 has reached 1,200 people. The arrival of Rohingya refugees to Indonesia is a serious problem that highlights humanitarian and international legal challenges. This often occurs as part of forced migration resulting from conflict, violence and human rights violations in their countries of origin, particularly in Myanmar. On May 17, 2024, two Rohingya ethnic refugee couples who were in the West Aceh Regent's Office Complex refugee camp, Meulaboh got married. However, there are no provisions in the Indonesian state that regulate the marriage of Rohingya immigrant couples. The aim of this research is to investigate the legal framework that regulates marriage rights for Rohingya refugees in Indonesia. It covers existing laws and policies and evaluates the extent to which the legal framework recognizes their marriage rights and the factors that constitute the legal challenges faced by Rohingya refugees in obtaining legal recognition of their marriages in Indonesia